Cortical Auditory Evoked Potentials in Children with a Hearing Loss: A Pilot Study. (12th January 2012) - Koravand, Amineh; Jutras, Benoît; Lassonde, Maryse
Abstract : Objective . This study examined the patterns of neural activity in the central auditory system in children with hearing loss. Methods . Cortical potentials and mismatch responses (MMRs) were recorded from ten children aged between 9 and 10 years: five with hearing loss and five with normal hearing in passive oddball paradigms using verbal and nonverbal stimuli. Results . Results indicate a trend toward larger P1 amplitude, a significant reduction in amplitude, and latency of N2 in children with hearing loss compared to control. No significant group differences were observed for the majority of the MMRs conditions. Conclusions . Data suggest that the reduced auditory input affects the pattern of cortical-auditory-evoked potentials in children with a mild to moderately severe hearing loss. Results suggest maturational delays and/or deficits in central auditory processing in children with hearing loss, as indicated by the neurophysiological markers P1 and N2. In contrast, negative MMR data suggest that the amplification provided by the hearing aids could have allowed children with hearing loss to develop adequate discriminative abilities.